Pengaruh Operational Complexity, Institutional Ownership, Leverage, dan Firm Size Terhadap Audit Report Lag pada Sektor Property & Real Estate - Siti Humairoh Juliani; Januar Eko Prasetio (Politeknik Ganesha Medan, 2026)
This research investigates the impact of operational complexity, institutional ownership, leverage, and firm size on audit report lag among property and real estate firms listed on the Indonesia Stock Exchange from 2021–2024. The prompt delivery of financial statements holds vital importance for stakeholders, although numerous sector-specific elements frequently result in substantial audit delays. Employing a quantitative methodology and purposive sampling, the study yields 285 observations derived from audited annual financial reports. Binary logistic regression analysis, conducted via SPSS version 25 software, assesses the likelihood of audit report lag occurrences. Findings reveal that institutional ownership exerts has a significant negative effect on audit report lag, indicating that higher institutional ownership strengthens the monitoring function and leads to faster audit completion. Conversely, leverage has a significant positive effect, suggesting that higher debt levels increase financial risk and require more extensive audit procedures, thus extending the audit process. Meanwhile, operational complexity and firm size exhibit no significant effects. Overall, audit report lag in the property and real estate sector is more strongly influenced by ownership structure and financial risk than by operational complexity or company size.